Smokers' Perceptions of Incentivized Smoking Cessation Programs: Examining How Payment Thresholds Change With Income. Issue 9 (23rd February 2021) - Breen, Rachel J; Ferguson, Stuart G; Palmer, Matthew A
Abstract: Introduction: Studies demonstrate that financial incentive programs increase smoking cessation. However, there is little guidance on which incentive magnitudes will ensure optimal enrollment and motivation levels. This study investigates current smokers' perceptions of varying incentive magnitudes to identify whether there is evidence for optimal amount(s) and whether perceptions differ by income group. Methods: Studies 1 ( N = 56) and 2 ( N = 147) were conducted online via Prolific.co. Current smokers were randomly shown multiple hypothetical incentive programs that differed only in the incentive amount offered. For each program, smokers rated its appeal and their likelihood of enrolling and predicted their motivation to quit if enrolled. Growth models were used to investigate the relationship between perspectives and the incentive amount. Results: An increasing quadratic trend in smokers' perceptions of programs as the incentive amount increased was identified. Incentive amounts beyond approximately £50–75 per week (£500–£750 total) did not significantly alter perceptions of programs. In Study 2, high-income smokers found programs significantly less appealing and motivating than low-income smokers, although no significant between-group differences were observed in the likelihood of enrollment. No significant differences were observed between low- and middle-income smokers. Conclusions: Increasing the incentive amount increased smoker's perceptions of programs. This relationship was curvilinear, meaning there may be a point beyond which further increasing the amount will not improve enrollment or motivation levels. Incentives appear equally appealing to low- and middle-income smokers; the population among whom smoking is most prevalent. Future research could explore other elements of program design and whether findings hold under real-world conditions. Implications: While acknowledging that they work, policymakers frequently request information about the monetary amount needed for incentive programs to be effective, and if this differs by income level. We investigated these questions using smokers' perceptions of hypothetical cessation programs that differed in the amount offered. An increasing quadratic trend in perceptions of programs by the amount and potential cut points was observed, suggesting a point may exist beyond which increasing the incentive will not improve perceptions of programs or enrollment levels. High-income smokers may not perceive incentives to be as appealing as other income groups, but appear equally willing to enroll.